2007
DOI: 10.1002/cncr.23220
|View full text |Cite
|
Sign up to set email alerts
|

Significance of age in acute myeloid leukemia patients younger than 30 years

Abstract: BACKGROUND. Data on the impact of age in acute myeloid leukemia (AML) patients <30 years treated in pediatric and adult trials are scarce. METHODS. In all, 891 patients <18 years were treated in the pediatric trials AML‐BFM 93/98 and 290 adolescents and young adults (>16 to <30 years) in the AMLCG 92/99 and AMLSG HD93/98A trials. Treatment schedules and dose intensities were comparable. RESULTS. Initial features and risk factors differed considerably between infants (<2 years) and older age groups and only sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 36 publications
(50 reference statements)
2
32
0
Order By: Relevance
“…With the rapid development of modern combination chemotherapy and hematopoietic stem cell transplantation, 5-year event-free survival for pediatric acute lymphoblastic leukemia (ALL) has been improved to rates as high as 80% [20,21]. However, the prognosis of pediatric AML is still poor, with long-term survival rates of about 50% to 65% [22]. The overall survival of CML was recently reported to be up to 80% at 8 years of follow-up in respondent patients due to the introduction of imatinib (a tyrosine kinase inhibitor) [23], there still remains a subset of patients who fail the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of modern combination chemotherapy and hematopoietic stem cell transplantation, 5-year event-free survival for pediatric acute lymphoblastic leukemia (ALL) has been improved to rates as high as 80% [20,21]. However, the prognosis of pediatric AML is still poor, with long-term survival rates of about 50% to 65% [22]. The overall survival of CML was recently reported to be up to 80% at 8 years of follow-up in respondent patients due to the introduction of imatinib (a tyrosine kinase inhibitor) [23], there still remains a subset of patients who fail the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the therapy should be to cure the patient by exterminating the leukemic clone while avoiding side effects and late effects as much as possible. In acute lymphoblastic leukemia, it has been shown that poorer prognosis of AYAs can be overcome with intensive pediatric protocols; whether a similar approach should be applied to AYAs with AML is not evidently provided [2]. Despite several strategies to increase the intensity of therapy, the long-term overall survival rate has not exceeded a plateau of 50%, suggesting that treatment-related toxicity does not balance against antileukemic efficacy [9].…”
Section: Managementmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) represents about 33% of adolescent and 50% adult leukemia [2]. In United States, using 1975–2011 US Surveillance Epidemiology and End Results (SEER) data, annual rates for new diagnosis of AML in AYAs are 4.4/100,000, but survival data for the specific age groups of AYA are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large survey evaluating the age effect on AML biology and response to therapy among pediatric patients [29], a clearly defined pattern was reported in the infancy age, but a distinct biology of AYAs could not be clearly identified. Large prospective studies that included both pediatric and adult patients did not report any special consideration or outcome for AYAs [30,31].…”
Section: Risk Stratification In Ayas - Adults or Children?mentioning
confidence: 99%